The birds, the bees and Erica: vulnerability of plant-pollinator communities in fragmented fynbos landscapes - Angoh, Siow Yan Jennifer (Percy FitzPatrick Institute of African Ornithology, 2016)
Habitat fragmentation has been identified as a major cause of pollination mutualism collapse that can eventually impinge on plants' reproductive success (e.g. through pollen-limitation). Agriculture, timber plantations, invasion by alien trees and the urbanisation of the southern Cape lowlands have transformed and fragmented large parts of the former distribution range of many Erica species. Recent evidence suggests that in the Fynbos biome, small remnants of natural and disturbed vegetation are likely to display depauperate plant communities. In the present study, it was found that Erica species richness declined significantly as patch size decreased. Limited nectar resources available on those small 'islands' might not be enough to attract essential bird and insect pollinators. Insect-pollinated species were more impacted by reduced patch size than the bird-pollinated ones. Further investigation using Erica discolor showed that for this widespread ornithophilous species, pollination mutualism still occurred in smaller fynbos patches. These findings stressed the importance of conserving small fragments for maintaining remnant plant populations, which can act as reliable food sources for avian pollinators. In addition, to cope with the effects of pollen limitation, highly resilient plant species have evolved and adopted different compensatory mechanisms. From a short-term perspective, adopting compensatory reproductive strategies (e.g. autonomous self-pollination, vegetative growth, and generalised pollination systems) could reduce dependence on specific pollinators and increase the chances of a species being able to persist through a period of low-pollinator abundance. The prevalence of autogamy and geitonogamy as alternatives to xenogamy was assessed in six different obligate seeder Erica species in the eastern coastal part of the Cape Floristic Region. Despite the long history of plantation-based timber production that fragmented the study area, and the subsequent possible pollinator loss, none of the species analysed in this study have adopted autonomous self-fertilisation as a response mechanism. Erica sessiliflora was the only species that showed a high compatibility for self-pollen. The species under investigation in a breeding system conducted here were also incapable of vegetative propagation and were plants targeting specific animal taxa (e.g. birds or insects) for successful pollination. Having limited compensatory mechanisms, further degradation of their habitat and weakening of their ecological interactions could be extremely detrimental to these Erica species' reproductive success.